Loss of Ambulation Due to Calcific Myonecrosis: A Rare but Reversible Complication of Wilson’s Disease - Abhishek Vaingankar; Divyani Garg; Ayush Agarwal; Divya M Radhakrishnan; Awadh Kishor Pandit; Madhavi Tripathi; Achal K Srivastava (Annals of Indian Academy of Neurology)
We report two cases of established Wilson’s disease (WD) presenting with calcific myonecrosis of the pelvic girdle in association with pelvic fractures. Despite initial improvement with chelation, subacute worsening of ambulation in both led to a consideration of neurologic deterioration on chelation therapy. However, evaluation revealed calcific myonecrosis of the hip joint and adjacent muscles as the cause. Both patients improved with intensive rehabilitation. A review of literature indicates that although osseomuscular complications are reported in WD, calcific myonecrosis is a hitherto unknown entity which, if recognized early, may be reversed, preventing disability and unnecessary change in chelation regimens.